Qatar : 2019 Article IV Consultation-Press Release; Staff Report. (IMF Staff Country Reports; Country Report ;, 2019)
This 2019 Article IV Consultation discusses that stronger real gross domestic product (GDP) growth is envisaged in the near term, with a recovery in hydrocarbon output. Medium-term growth will be buoyed by increased gas production and non-hydrocarbon growth. Expenditure consolidation would help to sustain fiscal and external surpluses. Ample liquidity will enable credit growth to support non-hydrocarbon GDP. Trade and geopolitical tensions could undermine investor confidence and weaken fiscal and external positions. The policy priorities are fiscal consolidation, strengthened fiscal policy frameworks, enhanced resiliency of the financial sector, financial inclusion, and a diversified economy. The financial sector remains sound, underpinned by strong profitability and capital. Strengthening the regulatory and supervisory frameworks would help to bolster financial stability. Attention to women's empowerment by introducing legislation emphasizing equality in remuneration and avoiding gender-based discrimination would support inclusive growth.